Hand Sanitizer Making Training for Women’s Farmer Group in Mojorejo Village, Jetis, Ponorogo - Mughniatul Ilma; Vicky Fitriani Herdiana (Institute for Research and Community Services, 2022)
Hand sanitizer could help clean one’s hands from germs and viruses, and thus, in a location where no handwashing is available, they could use hand sanitizer to clean their hands. Making hand sanitizer is very simple, and we could use plants found in one’s garden or yard. Limes and betels thrive in the garden owned by the Women's Farmer Group in Mojorejo Village, Jetis, Ponorogo Regency. These plants can be used to make hand sanitizer. However, the members of KWT had not known how to process them into hand sanitizer. This activity aimed to provide training for making hand sanitizer using natural ingredients picked from the KWT’s garden. As an alternative, we also trained the members of KWT about how to make hand sanitizer from artificial ingredients. We employed Asset Based Community Development (ABCD) method, which involves eight members of KWK in the village. We held an FGD to find the resources they had, and during the training, we demonstrated the procedures for making hand sanitizer. After the training, we also provided one-onone mentoring in making hand sanitizer. They made several kinds of hand sanitizer using natural and artificial ingredients. We interviewed two members of KWT after the training. They claimed that this activity had increased their knowledge about how to make use of the natural ingredients found in the garden, and that by making hand sanitizer by themselves, they could reduce their expenses.